Co-design of improved climbing bean production practices for smallholder farmers in the highlands of Uganda. (October 2019) - Ronner, E.; Descheemaeker, K.; Almekinders, C.; Ebanyat, P.; Giller, K.E.
Abstract: We evaluated the usefulness of a co-design process to generate a relevant basket of options for climbing bean cultivation in the context of a large-scale project. The aim was to identify a range of options sufficiently diverse to be of interest for farmers of widely-different resource endowment. The co-design process consisted of three cycles of demonstration, evaluation and re-design in the eastern and southwestern highlands of Uganda in 2014–2015. Evaluations aimed to distinguish preferences of farmers between the two areas, and among farmers of different gender and socio-economic backgrounds. Farmers, researchers, extension officers and NGO staff re-designed treatments for demonstrations in the next season. Climbing bean yields and evaluation scores varied between seasons and sites. Evaluation scores were not always in line with yields, revealing that farmers used multiple evaluation criteria next to yield, such as marketability of varieties, availability of inputs and ease of staking methods. The co-design process enriched the basket of options, improved the relevance of options demonstrated and enhanced the understanding of preferences of a diversity of users. Developing options for resource-poor farmers was difficult, however, because they face multiple constraints. The basket of options developed in this study can be applied across the East-African highlands, with an 'option-by-context' matrix as a starting point for out-scaling. The study also showed, however, that consistent recommendations about the suitability of technologies for different types of farmers were hard to identify. This highlights the importance of a basket of options with flexible combinations of practices rather than developing narrowly specified technology packages for static farm types. Highlights: Farmers, researchers and other stakeholders co-designed climbing bean options. Preference for options differed between farmers of different wealth and gender. Farmers' multiple evaluation criteria were incorporated in technology re-design. Finding suitable alternatives for resource-poor farmers remains challenging. Co-designed basket of options is applicable across the East African highlands.